95 DIHYDROTESTOSTERONE-INDUCED CONFORMATIONAL PERTURBATIONS IN ANDROGEN RECEPTOR: KINETIC AND THERMODYNAMIC INSIGHTS. (1st January 2006) - Jasuja, R.; Miksovska, J.; Bhasin, M.; Ganley, J.; Chandsawangbhuwana, S.; Baker, M.; Larsen, R. W.; Bhasin, S.
Abstract : Ligand binding to androgen receptor (AR) triggers a series of protein-protein interactions that result in receptor nuclear translocation and regulation of key transcriptional factors. It has been suggested that the agonist- and antagonist-bound AR assumes distinct conformational states that dictate the exposure of AR domains for co-activator and co-repressor recruitment; however, direct evidence of conformational change upon ligand binding has been lacking. As an understanding of agonist-induced conformational changes is imperative in rational design of selective androgen receptor modulators (SARMs), we determined the residue/helix specific conformational changes in AR utilizing molecular modeling, time resolved and steady-state biophysical spectroscopy. Methods and Results: Purified AR-ligand binding domain (AR-LBD) displays a biphasic decay of singlet excited state with two components, 1.8 ns and 1.1 ns (excitation -255 nm laser and emission collected through a 270 nm long-pass). In presence of DHT, only the 1.8 ns component is observed with a complete quenching of 1.1 ns. To identify domains where these residues are perturbed, second derivative spectroscopy calculations demonstrate that α/β ratio, denoting tyrosine and tryptophan solvent exposure, decreases drastically from 0.113 to 0.024. Molecular modeling, performed using biopolymer (Accelrys Insight II; CVFF force field, distance-dependent dielectric of 2), elucidates that residues 741, 789, and 746 spanning helices 7-8 and the linker are conformationally perturbed to accommodate DHT binding. These receptor rearrangements were found to be agonist specific, as casodex, an AR antagonist, did not induce these conformational changes. Conclusion: These data constitute the first demonstration that agonist binding to AR leads to conformational changes in the helices 7-8 and the linker region of AR that are not observed with an AR antagonist. This region harbors an LXXL motif that has been suggested to play an important role in selective recruitment of co-activators/co-repressors.